OPTIMALISASI PRODUKTIFITAS LAHAN KRITIS MELALUI PEMBUDIDAYAAN PEPAYA CALLINA DI DESA SETONO KECAMATAN NGRAMBE - Yuhanna, Wachidatul Linda; Dewi, Nurul Kusuma (Jurnal Terapan Abdimas, 2016)
Community empowerment with callina papaya cultivation is one form of utilization ground that have high economic value. Community usually only planted cassava and vegetables for daily consumption. Callina papaya is one of the crops that have high potential to sold, long harvest time, easy and simple treatment. Land use of Setono Ngrambe with Callina papaya cultivation is a creative solution for the development of natural resources and human resources to increase the income of society. This community service program carried out over 4 months including observation, training, mentoring and evaluation. Training and socialization going well and get good responses. Community enthusiastic following the training and socialization of papaya callina cultivation. In this training, community trained by team to do organic farming using cow urine fermentation. Material in this training include the introduction of papaya Callina, potential, and methods of cultivation. Government of Setono village make the Memorandum of Understanding that contains the community willingness to lend their land for planting Callina papaya in a supervision of IKIP PGRI MADIUN. Callina papaya can be excellent products and potentially make Setono Village as suppliers Callina papaya in East Java.Keywords: callina papaya, critical land, organic farming